The effects of a 4-week mesocycle of barbell back squat or barbell hip thrust strength training upon isolated lumbar extension strength - Hammond, A.; Perrin, C.; Steele, J.; Giessing, J.; Gentil, P.; Fisher, J. P. (PeerJ, 2019)
Objectives: Common exercises such as the barbell back squat (BBS) and barbell hip thrust (BHT) are perceived to provide a training stimulus to the lumbar extensors. However, to date there have been no empirical studies considering changes in lumbar extension strength as a result of BBS or BHT resistance training interventions. Purpose: To consider the effects of barbell back squat (BBS) and barbell hip thrust (BHT) resistance training programmes upon isolated lumbar extension (ILEX) strength. Methods: Trained male subjects (n=14; 22.07 ± 0.62 years; 179.31 ± 6.96 cm; 79.77 ± 13.81 kg) were randomised in to either BBS (n=7) or BHT (n=7) groups and performed 2 training sessions per week during a 4-week mesocycle using 80% of their 1RM. All subjects were tested pre- and post-intervention for BBS and BHT 1RM as well as isometric ILEX strength. Results: Analyses revealed that both BBS and BHT groups significantly improved both their BBS and BHT 1RM, suggesting a degree of transferability. However, the BBS group improved their BBS 1RM to a greater degree than the BHT group (p=0.050; ~11.8kg/10.2% vs. ~8.6kg/7.7%, respectively). And the BHT group improved their BHT 1RM to a greater degree than the BBS group (p=0.034; ~27.5kg/24.8% vs. ~20.3kg/13.3%, respectively). Neither BBS nor BHT groups significantly improved their isometric ILEX strength. Conclusions: The present study supports the concept of specificity, particularly in relation to the movement mechanics between trunk extension (including pelvic rotation) and ILEX. Our data suggests that strength coaches personal trainers, and trainees can self-select multi-joint lower body trunk extension exercises based on preference or variety. However, evidence suggests that neither the BBS nor BHT exercises can meaningfully increase isolated lumbar extension strength. Since strengthening these muscles might enhance physical and sporting performance we encourage strength coaches and personal trainers to prescribe ILEX exercise.